Synthesis and Spectral Studies of Some Transition Metal Complexes of Schiff Base - MAIHUB, A.A.; EL-AJAILY, M.M.; HUDERE, S.S. (Asian Journal of Chemistry, 2010)
The Schiff base has been prepared by condensing 4-[N,N-dimethylamino]benzaldehyde with o-aminophenol in ethanolic media, form three new metal complexes of the formulae of [NiL(OH)(H2O)].5H2O and [ML(OH)2(H2O)2].4H2O in which M represents Cr(III) or Fe(III) ion. These complexes were characterized by elemental analysis, molar conductance measurements, infrared and electronic spectra. The elemental analysis data exhibit the formation of 1 : 1 [M : L] ratio. The molar conductance measurements of the Schiff base complexes reveal the existence of non-electrolytic nature. Infrared spectral data display that the complexation occurs through oxygen atom of the hydroxyl group in the o-amino phenol ligand and the nitrogen atom of azomethine group. The electronic spectral data of the complexes suggest a square-planar geometry for Ni(II) complex and an octahedral structure for Cr(III) and Fe(III) complexes.